Effect of growth regulators in citral content in lemongrass in different seasons (in Portuguese) - Figueiredo, Roseane O. de [UNESP]; Delachiave, Maria Elena A. [UNESP] (My University, 2002)
The purpose of the present research was to evaluate the effect of plant growth regulators in yield citral content in lemongrass (Cymbopogon citratus (D.C.) Stapf), in different seasons. The field experiment was conducted on Sao Manuel Experimental Farm, Agronomical Science College, Paulista Estatal University, Botucatu, Brazil, which soil was classified in alic yellon red latosol (Haplorthox). Plants were randommly assigned blocks to treatments with three repetitions. The experimental groups consisted of GA3 (50 and 100 mg.l-1);Ethrel (100 and 200 mgl-1); CCC (500 and 1000 mg.l-1); Alar 85 (1000 and 2000 mg.l-1); Accel (20 and 40 mg.l-1) and control group. Five applications of plant growth regulators were realized every other three months. After 40 days of each foliar spray, the plants were cut and determined the citral yield. The essential oils were extracted from leaf tissue by hydrodistillation in a Clevenger apparatus. Samples of 250g of leaf and put in Clevenger apparatus with deionized water for 3h to determine the yield of essential oil. The citral content was analyzed by GC. In the present study the concentrations of plant growth regulators used did not increase citral content.
Keywords: Citral content; Cymbopogon citratus (DC.) Stapf-Essential oil; Growth regulator; Harvest time